Evaluating and improving the recovery aptitude of an automobile function: The PSA approach. (20th February 2004) - Coppens, C.; Le Coq, M.; Millet, D.; Michaud, P.
Today, limiting waste disposal has become a technical and an economical challenge. PSA Peugeot–Citroen, who undertook in the voluntary agreement of March 10, 1993, has developed a wider design methodology to improve the end of life vehicle (ELV) recovery rate. The aim of this methodology is to supply our designers and our suppliers with tools which allow us to evaluate and to improve the recovery aptitude of an automotive function (RAF). In order to develop this design methodology, a thesis was realised in collaboration with the CPN (Conception de Produits Nouveaux) laboratory of the ENSAM (Ecole Nationale Superieure d'Arts et Metiers) and the ADEME (Agence De l'Environnement et de la Matrise de l'Energie). This research began in October 1996 and was completed in September 1999. We will successively tackle in this document the research description (bibliographic study, need analysis), the design for recovery (DFR) tools (rules base and evaluations tools) and an experiment conducted on a front bumper of a Citroen Xsara Picasso.